A Flexible Client-Driven 3DTV System for Real-Time Acquisition, Transmission, and Display of Dynamic Scenes. (3rd June 2008) - Cao, Xun; Liu, Yebin; Dai, Qionghai
Abstract : 3D experience and free-viewpoint navigation are expected to be two essential features of next generation television. In this paper, we present a flexible 3DTV system in which multiview video streams are captured, compressed, transmitted, and finally converted to high-quality 3D video in real time. Our system consists of an8 × 8 camera array, 16 producer PCs, a streaming server, multiple clients, and several autostereoscopic displays. The whole system is implemented over IP network to provide multiple users with interactive 2D/3D switching, viewpoint control, and synthesis for dynamic scenes. In our approach, multiple video streams are first captured by a synchronized camera array. Then, we adopt a lengthened-B-field and region of interest- (ROI-) based coding scheme to guarantee a seamless view switching for each user as well as saving per-user transmission bandwidth. Finally, a convenient rendering algorithm is used to synthesize a visually pleasing result by introducing a new metric called Clarity Degree (CD). Experiments on both synthetic and real-world data have verified the feasibility, flexibility, and good performance of our system.